A Comparative Study on Gender and Fantastical Figures in Tolkien and Martin - Mr. Ashar Khan; Dr. Deepa Sehrawat (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Most of us are introduced to fairy tales and fantastical elements when we are growing up. We read the stories of warriors and princesses, dragons and demons, elves and dwarves, but what we do not realise at the moment is that the stories that we read in our childhood contain a deeper meaning behind them, as they portray the ideas of gender roles. While many studies have explored gender representation in fantasy literature, few have analysed how gender is constructed through an intersectional lens in both children’s stories and adult fiction. Which is why, understanding the portrayal of gender in these distinct literary categories offers deep insights into the sociocultural factors which influences character development and narrative structures. However, research comparing gender roles in Tolkien’s children's literature and Martin’s adult fiction remains limited. The main objective of this comparative study is to examine the intersection of gender with class, race, and power in J.R.R. Tolkien’s The Hobbit and The Lord of the Rings and George R.R. Martin’s A Song of Ice and Fire series. Drawing from feminist and intersectional theory, this study analyses how both authors depict gender roles, considering the impact of target audience and genre conventions. Data is gathered through textual analysis, focusing on key characters and their roles within the social and political hierarchies of their respective worlds. The analysis reveals that Tolkien’s characters embody more traditional, simplified gender roles with limited intersectionality, while Martin’s characters exhibit complex gender identities shaped by overlapping factors of power, class, and race.
Keywords: Patriarchy; Gender Roles; Feminism; Fantasy; Literature